2001
DOI: 10.1074/jbc.m007008200
|View full text |Cite
|
Sign up to set email alerts
|

Transcription Factors Zic1 and Zic2 Bind and Transactivate the Apolipoprotein E Gene Promoter

Abstract: We have used the yeast one-hybrid system to identify transcription factors that bind to specific sequences in proximal regions of the apolipoprotein E gene promoter. The sequence between ؊163 and ؊124, that has been previously defined as a functional promoter element, was used as a bait to screen a human brain cDNA library. Ten cDNA clones that encoded portions of the human Zic1 (five clones) and Zic2 (five clones) transcription factors were isolated. Electrophoretic mobility shift assays confirmed the presenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
56
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 64 publications
0
56
0
Order By: Relevance
“…The molecular mechanisms of Zic2 action during development remain unclear. Only a handful of direct targets for Zic2 have been identified (Yang et al, 2000;Salero et al, 2001;Sakurada et al, 2005), and an "optimal" consensus target binding sequence for Zic2 proteins is unknown. It has been suggested that its activation of target genes may be by unconventional means, such as recruitment of a DNA/RNA helicase, RHA (Ishiguro et al, 2007;Ishiguro and Aruga, 2008).…”
Section: Zic2 May Be Involved In the Regulation Of Other Target Genesmentioning
confidence: 99%
“…The molecular mechanisms of Zic2 action during development remain unclear. Only a handful of direct targets for Zic2 have been identified (Yang et al, 2000;Salero et al, 2001;Sakurada et al, 2005), and an "optimal" consensus target binding sequence for Zic2 proteins is unknown. It has been suggested that its activation of target genes may be by unconventional means, such as recruitment of a DNA/RNA helicase, RHA (Ishiguro et al, 2007;Ishiguro and Aruga, 2008).…”
Section: Zic2 May Be Involved In the Regulation Of Other Target Genesmentioning
confidence: 99%
“…Yeast one-hybrid assays have identified DNA binding sites for Zic proteins in the apolipoprotein E gene (three sites, each regulated by both Zic1 and Zic2), the dopamine receptor 1a gene (regulated by Zic2; the precise DNA binding sequence was not narrowed to less than 20 nucleotides), and the Math1 gene (regulated by Zic1) (Yang et al, 2000;Salero et al, 2001;Ebert et al, 2003). The Zic DNA binding sites in these genes are quite different, although all are GC-rich (Aruga, 2004; Table 1C).…”
Section: Direct Targets Of Zic Proteinsmentioning
confidence: 99%
“…Multiple potential control elements for apoE gene expression have been described in its 5Ј proximal promoter (15)(16)(17)(18)(19). In addition, downstream control elements have been described that are required to direct specific expression of apoE in various tissues.…”
mentioning
confidence: 99%